Syntactic constructions involving verbs of elocution in West Greenlandic - Berge, Anna (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2002)
AbstractThis article seeks to demonstrate, on the basis of textual evidence in the historical period of West Greenlandic, that there exists an indirect speech construction in this language, even if there is a marked preference for direct speech strategies.